Thermophilic Aerobic Digestion of Food Waste to Pelletized Fertilizer - a/l Muniandy, Devendraa (IRC, 2016)
In this report, thermophilic aerobic digestion of food waste is being introduced to convert the food waste into a pelletized fertilizer for economical usage. In overall, many statistics been shown in this report about the generation of food waste globally and also particularly in Malaysia. Even, ways of managing the municipal solid waste particularly food waste also been revealed in this report. The objectives of this research project is mainly to study the effect of thermophilic aerobic temperature on the degradation of food waste, determining the composition of the produced fertilizer and also analysing the moisture content of the food waste. Moreover, the scope of study of this whole research paper comprehensive more on the understanding the aerobic thermophilic condition on the digestion of food waste into fertilizers, densifying the fertilizers into pellets and analyzing the percentage content of carbon, nitrogen and phosphorus in the fertilizer.